Health at older ages : the causes and consequences of declining disability among the elderly - Cutler, David M.; Wise, David A. (University of Chicago Press, 2008)
Americans are living longer--and staying healthier longer--than ever before. Despite the rapid disappearance of pensions and health care benefits for retirees, older people are healthier and better off than they were twenty years ago. In Health at Older Ages, a distinguished team of economists analyzes the foundations of disability decline, quantifies this phenomenon in economic terms, and proposes what might be done to accelerate future improvements in the health of our most elderly populations. This breakthrough volume argues that educational attainment, high socioeconomic status, an older ret.
"This volume consists of papers presented at a conference held in Jackson Hole, Wyoming, in October 2004"--Page xi
Keywords: Older people -- Health and hygiene -- United States -- Statistics.; Older people with disabilities -- United States -- Statistics.; Older people.; People with disabilities.; Aged; Geriatric Assessment; Chronic Disease -- economics; Chronic Disease -- prevention & control; Persons with Disabilities; Health Services for the Aged -- trends; United States; Personnes âgées -- Santé et hygiène -- États-Unis -- Statistiques.; Personnes âgées handicapées -- États-Unis -- Statistiques.; Personnes âgées.; Personnes handicapées.; elderly.; MEDICAL -- Geriatrics.; MEDICAL -- Nursing -- Gerontology.; People with disabilities; Older people; Older people -- Health and hygiene; Older people with disabilities; Statistics